Peripheral DNA methylation, cognitive decline and brain aging: pilot findings from the Whitehall II imaging study. (25th April 2018) - Chouliaras, Leonidas; Pishva, Ehsan; Haapakoski, Rita; Zsoldos, Eniko; Mahmood, Abda; Filippini, Nicola; Burrage, Joe; Mill, Jonathan; Kivimäki, Mika; Lunnon, Katie; Ebmeier, Klaus P
Aim: The present study investigated the link between peripheral DNA methylation (DNAm), cognitive impairment and brain aging.Methods: We tested the association between blood genome-wide DNAm profiles using the Illumina 450K arrays, cognitive dysfunction and brain MRI measures in selected participants of the Whitehall II imaging sub-study.Results: Eight differentially methylated regions were associated with cognitive impairment. Accelerated aging based on the Hannum epigenetic clock was associated with mean diffusivity and global fractional anisotropy. We also identified modules of co-methylated loci associated with white matter hyperintensities. These co-methylation modules were enriched among pathways relevant to β-amyloid processing and glutamatergic signaling.Conclusion: Our data support the notion that blood DNAm changes may have utility as a biomarker for cognitive dysfunction and brain aging.